Becoming religious in a secular age - Elmore, Mark (University of California Press, 2016)
"Religion is commonly imagined as a timeless component of human inheritance, but in the Western Himalayas the community of Himachal Pradesh discovered their religion only after India became an independent secular state. Based on extensive ethnographic and archival work, Becoming Religious in a Secular Age narrates their discovery and the ways it transformed their relations to their pasts, to themselves, and to others. And as Mark Elmore demonstrates, Himachali religion offers a unique opportunity to reimagine relations between religion and secularity more generally. Tracing the emergence of religion as a widely accepted category, Elmore shows that modern secularity is not so much the eradication of religion as the very condition for its emergence. To become modern ethical subjects is to become religious, and this book creatively augments our understanding of both religion and modernity"--Provided by publisher